Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1089/vbz.2016.1979
|View full text |Cite
|
Sign up to set email alerts
|

Canine Infections and Partial S Segment Sequence Analysis of Toscana Virus in Turkey

Abstract: Introduction: Toscana virus (TOSV) is a sandfly-borne bunyavirus with a significant public health impact. Preliminary studies have revealed TOSV exposure in dogs and they were suggested as potential reservoirs. This study was performed to characterize canine TOSV infections in an endemic region. Sequencing of TOSV small (S) segment in several previously identified specimens was also undertaken to reveal viral genealogy. Materials and Methods: Canine and feline plasma were collected in several districts of Mers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
1
12
1
Order By: Relevance
“…In the present study no association between the presence of antibodies to L. infantum and TOSV was detected (only six dogs were seropositive for both pathogens), not corroborating the epidemiological relationship between human [ 22 ] and canine [ 38 ] leishmaniosis and TOSV infection previously suggested. Nevertheless, the seroprevalence rate obtained in dogs in the present study, together with the seroprevalence detected in humans (ranging from 2% in control population to 4.2% in population with central nervous system disease) [ 10 ] and the reports of human cases of TOSV meningitis [ 9 , 10 ] demonstrate the circulation of the virus or TOSV-like viruses in Portugal.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In the present study no association between the presence of antibodies to L. infantum and TOSV was detected (only six dogs were seropositive for both pathogens), not corroborating the epidemiological relationship between human [ 22 ] and canine [ 38 ] leishmaniosis and TOSV infection previously suggested. Nevertheless, the seroprevalence rate obtained in dogs in the present study, together with the seroprevalence detected in humans (ranging from 2% in control population to 4.2% in population with central nervous system disease) [ 10 ] and the reports of human cases of TOSV meningitis [ 9 , 10 ] demonstrate the circulation of the virus or TOSV-like viruses in Portugal.…”
Section: Discussioncontrasting
confidence: 68%
“…and different sand fly-borne phleboviruses in the insect on one hand [ 35 , 36 ] and in dogs on the other hand [ 17 ] have been reported. In addition, the detection of L. infantum and TOSV and Massilia virus in phlebotomine sand flies [ 13 , 37 ], humans [ 22 ] or dogs [ 38 ] sharing the same environmental area has also been described. Thus, we evaluated if the seroprevalence to one of the tested pathogens was significantly associated with seroprevalence to the others.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary Table 5 shows that 43 strains fall into this category, and that three Turkish strains (Thr2012, Ank2012 and pu3) are candidate reassortants with L segments of genotype A and S segments of genotype B. However, this must be treated with caution, since the Turkish sequences concerned were derived in two separate studies (Dincer et al, 2016; Ergunay et al, 2015) and although the authors noted the genotype in each case to be the same as that given in Supplementary Table 5, no mention was made of reassortment. It is not clear from the accompanying papers if the strain designation really indicates that each is derived from a single individual.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that neutralizing antibodies against TOSV have been repeatedly described in dogs (4.3-8.4% in studies conducted in France, Portugal, Tunisia, Algeria, Greece, and Cyprus) is likely to reflect exposure rather than being indicative of a more peculiar role in the natural cycle [74,[76][77][78][79][80]. However, two studies conducted in dogs from Mediterranean Anatolia (Turkey) reported the presence of TOSV RNA in the blood of approximately 3% and 10% of tested dogs, respectively, of which some were co-infected with Leishmania parasites [82,83]. Co-infection could contribute to this apparent active replication of TOSV.…”
Section: Vertebrates As Possible Reservoir or Amplification Hostmentioning
confidence: 98%